Understanding how capping of actin filaments prevents epithelium to mesenchymal like transitions in genetically defined epithelial tissues - Rebelo, Sofia Raquel Paulo (2010)
Tese de mestrado, Biologia (Biologia Evolutiva e do Desenvolvimento), 2007, Universidade de Lisboa, Faculdade de Ciências